Effect of Training and Motivation on the Work of Employees' Performance in Tribhuvan University - Neupane, Bashu; Luitel, Ananta Jivan (DEPAN, 2024)
This research aims to evaluate the impact of motivation and training on the performance of employees at Tribhuvan University in the Kathmandu Valley. Data was collected using self-structured questionnaires administered to 86 T.U. employees working in the Kathmandu Valley. A 5-point Likert scale was used to gather the primary data. The reliability and validity of the data were assessed using Cronbach's alpha, which yielded a value of 0.702, indicating that the independent variables may significantly explain the dependent variable. Descriptive statistics were applied to examine the characteristics of the data, while regression analysis was utilized to investigate causal relationships. The study highlights the importance of motivation and training in enhancing employee performance at Tribhuvan University in the Kathmandu Valley.